Polymethoxylated flavones from the leaves of Vitex negundo have fungal-promoting and antibacterial activities during the production of broad bean koji - Liu, Jiayi; Xu, Yetong; Yan, Jianyu; Bai, Liping; Hua, Juan; Luo, Shihong (Frontiers in Microbiology, 2024)
Broad bean paste is a popular condiment in Asian countries. Leaves of Vitex negundo Linn. were used extensively in China during the koji-making of broad bean paste. Spreading V. negundo leaves on raw broad beans during fermentation was able to facilitate the rapid growth of fungi to form mature koji. We isolated two strains of fungi from mature koji, and four strains of bacteria from the rotten broad beans resulting from a failed attempt. According to microbial activity assays, two polymethoxylated flavones, 5-hydroxy-3,6,7,8,3′,4′-hexamethoxy flavone (HJ-1) and 5,4′-dihydroxy-3,6,7,8,3′-pentamethoxy flavone (HJ-2) were isolated from V. negundo leaves, and the fungal growth promotion and inhibition of bacterial growth of these two compounds were found to improve the production of broad bean koji. This study reveals the compounds present in V. negundo leaves with bioactivity against important microbes in koji manufacture, and provides a theoretical basis for the application of V. negundo in broad bean paste production.